Clearing the smokescreen: The current evidence on cannabis use - Margriet van Laar (Frontiers Research Topics, 2015)
Cannabis remains the most commonly used illicit substance world-wide, with international estimates indicating that 2.8%-4.5% of the global population use cannabis each year. This prevalence rate has not changed substantially in the past decade and there is no indication that it will do so in the next decade. In line with this, many prominent organizations and individuals have acknowledged that the "war on drugs" has failed and are now calling for a rethink on drug-related policy and legal frameworks. With a growing number of jurisdictions across the world heeding this call and introducing legislation to decriminalize or legalize cannabis use, it is essential that any changes to legal frameworks and public health policies are based on the best available scientific evidence. To facilitate the adoption of an evidence-based approach to cannabis policy, the aim of this Research Topic was to gather a comprehensive body of research to clarify the current state of evidence relating to cannabis use. Of interest were articles addressing the following questions: • How do we study cannabis use? (e.g., recruitment; measuring dose/use; assessing dependence/problematic use; confounding; translation of findings from animal studies) • What do we know about cannabis use? (e.g., patterns, contexts, methods of use) • What do we know about people who use cannabis? (e.g., who uses cannabis and why) • What are the social settings, norms and cultural values that go along with cannabis use? • How is problematic cannabis use, as opposed to mere use, defined, judged and constructed in different societies? • What do we know about the effects/outcomes of cannabis use? (e.g., acute, short- and long-term; harms/ benefits) • What do we know about the factors associated with the initiation, continuance and cessation of cannabis use? • What do we know about the medicinal use of cannabis? (e.g., who uses medicinally and why; efficacy/effectiveness in different clinical populations; comparison with other medications) • What do we know about treatment for people who engage in problematic cannabis use? (e.g., who seeks/is referred to treatment and why; efficacy and effectiveness) • What do we know about cannabis? (e.g., pharmacodynamics/pharmacokinetics of different strains, cultivation, preparation and consumption methods) • How do policy and legal frameworks impact on the people who use cannabis? • What is the future for cannabis research? (e.g., potential avenues for future research; aspects needing more attention; innovative approaches; political/funding issues affecting cannabis research)